PENGARUH KOMPETENSI GURU DAN KOMITMEN PROFESIONALISME GURU TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DI SDN 3 SUNGAILIAT - Sari, Deby Novita; Rizaldi, Rizaldi; Hidayat, Wahyu (Publicio: Jurnal Ilmiah Politik, Kebijakan dan Sosial, 2023)
The purpose of this study was to determine teacher competence and teacher professionalism commitment to organizational citizenship behavior (OCB) at SDN 3 Sungailiat. This research was conducted in a quantitative way. Data were collected through questionnaires and documentation. The sample was taken through a survey. Data analysis was conducted through multiple linear regression analysis, t test analysis, f test analysis, and ditermination analysis. The results showed that teacher competence affects Organizational Citizenship Behavior (OCB), as shown by the t-test value of 0.028, which is lower than the probability value of 0.05. Teachers' professional commitment also affects OCB, as shown by the t-test value of 0.000, which is lower than the probability value of 0.05.Teachers' competence and teachers' professional commitment, both X variables, make a considerable contribution, 78.6%. Other factors not examined in the study made a smaller contribution. The result is that teacher competence and commitment have a positive influence on OCB. The higher the competence and commitment of a teacher, the higher OCB they have. Suggestions for principals to continue to improve teachers' abilities and commitment to the school.